IDENTIFIKASI FAKTOR KEMENARIKAN TEMPAT SEBAGAI PEMBENTUK RASA ATTACHMENT PENGUNJUNG PADA BANGUNAN YANG MENGALAMI TRANSFORMASI FUNGSI: IDENTIFIKASI FAKTOR KEMENARIKAN TEMPAT SEBAGAI PEMBENTUK RASA ATTACHMENT PENGUNJUNG PADA BANGUNAN YANG MENGALAMI TRANSFORMASI FUNGSI - Vika Haristianti (Universitas Telkom, 2026)
Abstract : The coffee shops in Bandung is no longer just a passing fad. It is estimated that there are currently around 600 coffee shops in operation. Another factor driving the growth of the café scene is the public’s growing obsession with social media. This research intends to identify attractive factors in coffee shops with hidden gem branding, which are located in spaces that have undergone functional transformation. This was done because, in Bandung, the trend of stable consumer development means that coffee shops are no longer just a seasonal trend. This research is a cross-sectional study and was analyzed quantitatively. Data collection methods were carried out using field observations and the distribution of questionnaires, as well as literature studies. The research results show that the author's hypothesis which suggests attractiveness factors in coffee shops with hidden gem branding that are located in spaces that have undergone functional transformation, is related to visitors' sense of attachment to the physical space of the coffee shop. The characteristics that feel the element of attachment the most are visitors aged 17 – 25 years. Characteristic of spatial transformation, the insertion system is considered to create a feeling of familiarity because it reminds visitors of their memories when they were in the case study coffee shop area due to not making many changes, thus influencing the feeling of familiarity. The design variables that cause the desire to revisit, because they cause attachment, are the variables of staff friendliness, room ambiance, furniture layout, furniture design, level of privacy, and room size. Keywords : coffee shop, hidden gem, spatial transformation, commodification, place attachment